Engaging Students in a Mock Town Hall Discussion: Case Study of the Big Thorne Timber Sale. Issue 1 (20th December 2016) - Flaherty, Elizabeth A.; Eckrich, Carolyn A.; Ben-David, Merav
Abstract : Core Ideas: Provides students with a problem‐solving and decision‐making experience. Highlights U.S. policy involved in managing our natural resources. Describes an actual natural resource management situation in southeastern Alaska. Students represent stakeholders and debate the issue in a simulated public meeting. After nearly two decades of little to no logging activity on Prince of Wales Island (POW), Alaska, part of the Tongass National Forest, the USDA‐Forest Service proposed a new plan to harvest approximately 2500 ha (6000 acres) of old‐growth forest. The island has experienced over 60 years of harvest that has significantly affected various natural resources. In natural resource management and planning, addressing the needs of multiple stakeholders is often the greatest challenge for development of a management plan. On POW, stakeholders include those benefiting from timber harvest and the logging industry, non‐consumptive users including tourists, fishing and hunting enthusiasts, and local residents. This case simulates a real‐life town hall meeting designed to inform managers of the concerns of various stakeholders before choosing between several alternative plans. Students representing the different stakeholder groups collect supporting information related to the Big Thorne Timber Sale, and then present their case in a simulated public meeting and debate the pros and cons of the proposed harvest. The objective of this case, designed for a lower‐level course, is to expose students to the complexities of natural resource management when addressing the concerns of multiple stakeholders. It also provides students with an opportunity to debate a natural resource topic based on their investigation as well as engage in public speaking.